HIDROLISIS DAN HIDROGENASI SEREMPAK SELULOSA MENJADI SORBITOL - Christina Puspaningtyas, Yohana
Sorbitol is one of chemical product with high value that can be produced through glucose hydrogenation. Apart from starch, cellulose hold a great potential for a source of glucose. Which can be produce using cellulose decomposition through hydrolysis reaction. Hydrogenation reaction is used to produce sorbitol from glucose. Sorbitol is one of the commonly use commodity as a material in pharmaceutical and food industry. Sorbitol also hold a potential in the energy industry. This is research is design with the scope of hydrolytic and hydrogenation of cellulose in the temperature of 65oC and 100oC and 1 bar of pressure. The catalyst used in hydrolysis reaction Is a variation of aspartic acid and hydrochloric acid in the formic acid solution with a certain concentration. The catalyst used in hydrogenation reaction is nickel aspartate. Hydrogen is supplied with dehydrogenation reaction of formic acid using mass varied molybdic acid. The objective of this research is to determine the product yield in the hydrolysis and hydrogenation reaction. The variant with the most significant yield then used to calculate the product yield for the simultaneous hidrolysis and hydrogenation reaction of cellulose into sorbitol. The research has found that aspartic acid was able to produce glucose with 0.6 ???? 6.7 % yield and hydrochloric acid was able to produce with 9.6 ???? 16.5% yield. Sorbitol produced from the hydrogenation reaction has 12% and 14% yield. These data then use to calculate the yield for the simultaneous reaction. The theoretical yield of sorbitol is 1,35% and 8,32 for glucose. Most of the mass percentage is unreacted cellulose and the product from the glucose degradation reaction.